1975
DOI: 10.1136/bmj.1.5953.299
|View full text |Cite
|
Sign up to set email alerts
|

Bromocriptine treatment of acromegaly.

Abstract: SummaryThe effects of oral bromocriptine in acromegaly have been studied. A dose of 5 mg six-hourly suppressed circulating growth hormone (GH) levels in nine out of 11 patients treated for seven to 11 weeks. This was associated with considerable clinical improvement in all patients, with abolition of excessive sweating, reduction in softtissue thickening, loosening of rings, decrease in shoe size, improvement in facial features, and loosening of dentures. Metabolic changes included improvement in glucose toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
2

Year Published

1976
1976
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(63 citation statements)
references
References 19 publications
4
57
0
2
Order By: Relevance
“…The present findings might be of therapeutic importance, since suppression of the release of diabetogenic hormones like hOR and hPRL with bromocriptine in endocrine disturbances like acromegaly [20], hyperprolactinaemia or juvenile-type diabetes mellitus (Landgraf et al, unpublished observation) might improve the metabolic disturbances seen in these patients.…”
Section: Discussionmentioning
confidence: 64%
“…The present findings might be of therapeutic importance, since suppression of the release of diabetogenic hormones like hOR and hPRL with bromocriptine in endocrine disturbances like acromegaly [20], hyperprolactinaemia or juvenile-type diabetes mellitus (Landgraf et al, unpublished observation) might improve the metabolic disturbances seen in these patients.…”
Section: Discussionmentioning
confidence: 64%
“…Though many investigators (Thorner et al, 1975;Halse et al, 1977;Eskildsen et al, 1978;Dunn et al, 1977;Meneschi, 1980) reported that without long-term treatment, a responder to bromocriptine cannot be separated from a non-responder in acromegaly, other authors (Nortier et al, 1984;Belforte et al, 1977;Oppizzi et al, 1984) GH responses to the TRH test in evaluating the effect of bromocriptine therapy. In the present study, we observed that the effects of bromocriptine diminished in 2 of 18 patients during long-term therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine agonists Dopamine D 2 receptor agonists have been used to treat acromegaly since the 1970s (52,53). Their overall efficacy is, however, limited in comparison with other therapeutic modalities.…”
Section: Gh Receptor Antagonistmentioning
confidence: 99%